Intervensi Kebijakan Pasca (Dis)integrasi: Sebuah Pendekatan Resolusi Konflik - Lele, Gabriel (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2001)
Nation-state has now been challenged by many forces for not be able to fully meet its citizens aspirations. These challenges have put the fate of national integration on the brink of bankruptcy. But beyond that challenges, nation-state has systematically grown as a strong actor in both national and international arena. The question is how to bridge those two contradictory phenomena. Herein, several strategic interventions of public policy can be adopted Consociational democracy, representative bureaucracy, local autonomy and federalism are but some suggested alternatives. For Indonesia, the last two alternatives are far more feasible than the first two. But since federalism is sometimes resisted by central government and used no more than a political arsenal by those of politicians, then local autonomy comes to the fore to be the focal agenda. Thus, the challenge ahead is to realize local autonomy by accommodating those strategic values of federalism such as opening power window to broader public participation, respecting pluralism, and enforcing political and economic justice. This last point is the theme of this paper.